2022
DOI: 10.1021/acsanm.2c01091
|View full text |Cite
|
Sign up to set email alerts
|

DNA Scaffolds with Manganese Oxide/Oxyhydroxide Nanoparticles for Highly Stable Supercapacitance Electrodes

Abstract: The utilization of manganese oxides/oxyhydroxides as efficient supercapacitor electrode materials is limited by their cyclic stability and thus restricted for practical applications. One attractive approach for improving their stable electrochemical performance is to form a hybrid with suitable support materials. Herein, we describe the fabrication of manganese oxide/oxyhydroxide nanoparticle (MONP)embedded deoxyribonucleic acid (DNA) scaffolds using a simple magnetic stirring and drop-casting method. The phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The ability of DNA to self-assemble nanostructures, along with the accuracy of nanoparticle localization on DNA scaffolds, presents a potential strategy for the self-organization of composite nanostructures (Winfree et al 1998 ; Park et al 2008b ; Li et al 2018 ; Nakata et al 2019 ; Komarala et al 2022 ). Muller et al reported for the first time on the production of heterodimerase complexes of Glucose Oxidase (GOX) or Horseradish peroxidase (HRP) through DNA-directed assembly of enzyme oligonucleotide conjugates.…”
Section: Strategies Of Enzyme Immobilization Mediated By a Scaffoldmentioning
confidence: 99%
“…The ability of DNA to self-assemble nanostructures, along with the accuracy of nanoparticle localization on DNA scaffolds, presents a potential strategy for the self-organization of composite nanostructures (Winfree et al 1998 ; Park et al 2008b ; Li et al 2018 ; Nakata et al 2019 ; Komarala et al 2022 ). Muller et al reported for the first time on the production of heterodimerase complexes of Glucose Oxidase (GOX) or Horseradish peroxidase (HRP) through DNA-directed assembly of enzyme oligonucleotide conjugates.…”
Section: Strategies Of Enzyme Immobilization Mediated By a Scaffoldmentioning
confidence: 99%
“…[ 2 ] The research on supercapacitors has greatly promoted the development of new intelligent devices. [ 3 ] Namely, double‐layer capacitors, known for their fast and stable energy storage performance as well as environmentally friendly properties, have been widely studied by researchers. [ 4 ] Additionally, metal‐organic frameworks (MOFs) are one of the most popular electrode materials because of their large pores, flexible preparation methods, and controllable structures.…”
Section: Introductionmentioning
confidence: 99%
“…Deoxyribonucleic acid (DNA) has been the primary material of interest due to its distinct properties, including high dielectric constant, large bandgap and high transparency. Pristine DNA(D) and cetyltrimethylammonium chloride (CTMA) surfactant-modified DNA (CD) can extend utility in inorganic-and organic-based devices and sensor applications [6][7][8][9][10]. Furthermore, DNA can be utilized as an efficient template for hosting drugs, dyes, ions and nanoparticles for enhancing functionality [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%